Studies on Fermentative Transformation of Molasses to Citric Acid by A. niger Exposed to Some Chemical Mutagens - Singh, S.P.; Verma, A.K.; Singh, B.K.; Kamal, K.P. (Asian Journal of Chemistry, 2010)
Mutagenic action of 1,1-dimethyl hydrazine, 1,2-dimethyl hydrazine dihydrochloride, hydrazine sulphate an hydrazine acetate were studied on fermentative transformation of molasses to citric acid by A. niger. It was found that hydrazine sulphate and hydrazine acetate enhance the production of citric acid to a great extent while 1,1-dimethyl hydrazine and 1,2-dimethyl hydrazine dihydrochloride retard the yield.